2018
DOI: 10.1111/1442-1984.12219
|View full text |Cite
|
Sign up to set email alerts
|

Effects of seed hydration memory on initial growth under water deficit of cactus from two populations that occur in different ecosystems in Northeast Brazil

Abstract: Discontinuity during the rehydration process of seeds that germinate in arid and semi‐arid ecosystems leads to the occurrence of hydration and dehydration cycles (HD cycles). HD cycles play an important role in the persistence and dynamics of plants in these ecosystems. Pilosocereus catingicola subsp. salvadorensis is a cactus that occurs in different ecosystems of northeast Brazil. This species is submitted to different environmental conditions, such as irregularity of soil water availability. This factor dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 14 publications
(37 reference statements)
1
11
0
2
Order By: Relevance
“…However, this adaptive response was only observed when exposure to the conditioning priming agent in seeds occurred moderately, with no positive response to a long-term condition (Singh et al, 2014;Thomas et al, 2020). Our results are partially in line with this statement, demonstrating that seedlings from seeds that have undergone two cycles of HD (moderate exposure), associated with moderate stress exposures, seem to accumulate greater acclimatizing stress responses, such as increased biomass production and leaf area, a behavior also observed by Lima and Meiado (2018b) in Cactaceae. In its turn, the benefits of exposure to the three HD cycles (long-term condition) manifest into greater regulation of RGR in stem diameter and leaf number, and maintenance of RWC even under the most severe stress.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…However, this adaptive response was only observed when exposure to the conditioning priming agent in seeds occurred moderately, with no positive response to a long-term condition (Singh et al, 2014;Thomas et al, 2020). Our results are partially in line with this statement, demonstrating that seedlings from seeds that have undergone two cycles of HD (moderate exposure), associated with moderate stress exposures, seem to accumulate greater acclimatizing stress responses, such as increased biomass production and leaf area, a behavior also observed by Lima and Meiado (2018b) in Cactaceae. In its turn, the benefits of exposure to the three HD cycles (long-term condition) manifest into greater regulation of RGR in stem diameter and leaf number, and maintenance of RWC even under the most severe stress.…”
Section: Discussionsupporting
confidence: 85%
“…However, some studies with plants from Caatinga, a Brazilian Tropical Dry Forest, have demonstrated that, sometimes, discontinuous hydration do not favor germination in adequate water availability, but it does benefit the process in drought or salt stress condition (Lima & Meiado 2017;Lima & Meiado 2018b). On the other hand, some observation has showed that, for some species, the benefit of discontinuous hydration has been recognized during plant initial growth (Lima & Meiado 2018a) or during stress environmental conditions conferring to drought or salt-tolerance (Lima & Meiado 2018b).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have already demonstrated the benefits of hydropriming in relation to the time required for seeds to germinate (Contreras-Quiroz et al, 2016;Lima and Meiado, 2017;2018a;2018b;Lima et al, 2018). In these works, carried out on species that also occur in the Caatinga seeds that ondergone HD cycles significantly decreased the germination time This acceleration of germination speed can be beneficial for seeds to germinate and for seedlings to establish themselves in more favorable times and not be exposed to other environmental adversities, such as water Journal of Seed Science, v.43, e202143004, 2021 scarcity, contamination by pathogens, predation, among others.…”
Section: Resultsmentioning
confidence: 97%
“…Hydropriming can be limited by the amount and time of exposure of seeds to water or conditioning agents. In natural conditions, seeds can undergo several short cycles of hydration and dehydration, which would lead to a greater tolerance to high temperatures at which seeds are exposed to germinate in this semiarid ecosystem (Lima and Meiado, 2017;2018a;2018b;Lima et al, 2018). Cycles of hydration and dehydration of seeds provide biochemical changes, such as mobilization of protein storage, mainly globulins and prolamins (Aragão et al, 2002), synthesis of stress proteins and late embryogenesis proteins (LEA) (Bray, 2004), and accumulation of organic solutes (Matias et al, 2015) allowing seeds to cope better with drought periods, such as the predicted by future climate scenarios (IPCC, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Acerca dos resultados obtidos nesta pesquisa em relação a tecnologia do Hydropriming, descritos nas Tabela 1 -3, servem de base para a discussão sobre os seguintes pontos. Primeiro, sementes provenientes da Caatinga apresentam memória hídrica, com eventos de hidratação e desidratação sendo integrantes deste processo, segundo afirma Lima & Meiado (2018), sendo assim, a utilização de longos períodos contínuos de imersão em água poderiam não ser convenientes para algumas populações e espécies provenientes deste bioma. Também, fazendo um paradoxo sobre o escrito de Pereira (2011) e Ferreira et al (2021, pode ser percebido que sementes provenientes de populações vegetais do bioma Caatinga apresentam comportamentos diferentes em relação a promoção de germinação e vigor, em relação a utilização da imersão em água pelo período de 24h.…”
unclassified